1996
DOI: 10.1097/00000542-199604000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Analgesic Effect of Ropivacaine during Continuous Epidural Infusion for Postoperative Pain Relief

Abstract: The pharmacokinetics of ropivacaine were independent of dose, but total clearance decreased with time over 24 h. The consistent increase in total plasma concentration during the postoperative epidural infusion contrasted to much less variation in the unbound plasma concentrations of ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
3
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 14 publications
3
25
3
2
Order By: Relevance
“…Threshold levels for central hours and the end of the infusion suggests that a steady state was not reached after 48 hours. Although only an estimate of the actual value, these observations strongly contrast with previous studies that reported stable unbound concentrations during continuous infusion (11,14,20). A possible explanation is variability in the intrinsic metabolic clearance of ropivacaine (CL int ), assuming that the hepatic extraction ratio of ropivacaine is low and the intrinsic clearance corresponds to the unbound clearance (CL u ).…”
Section: Discussioncontrasting
confidence: 62%
“…Threshold levels for central hours and the end of the infusion suggests that a steady state was not reached after 48 hours. Although only an estimate of the actual value, these observations strongly contrast with previous studies that reported stable unbound concentrations during continuous infusion (11,14,20). A possible explanation is variability in the intrinsic metabolic clearance of ropivacaine (CL int ), assuming that the hepatic extraction ratio of ropivacaine is low and the intrinsic clearance corresponds to the unbound clearance (CL u ).…”
Section: Discussioncontrasting
confidence: 62%
“…For highly proteinbound drugs such as ropivacaine, small changes in protein binding will have significant effects on the unbound concentration [14].…”
mentioning
confidence: 99%
“…This may be due to the fact that factors other than plasma AAG concentration may alter the relationship between plasma AAG concentration and unbound drug. Erichsen et al [14] noted that alterations in plasma AAG concentration in a surgical population accounted for only 50% of the observed variation in unbound ropivacaine concentrations. In our study, umbilical venous AAG concentration was 5.25 (1.8) mmol.l 21 , similar to concentrations noted by Irestedt et al [15] in parturients undergoing elective operative delivery under ropivacaine epidural anaesthesia at term.…”
mentioning
confidence: 99%
“…2 Epidural opioids combined with local anesthetic solution improve the quality of postoperative analgesia reducing the dose related adverse effects of either class of drug alone. [3][4][5] Ropivacaine is a new, long-acting local anesthetic with a more favourable toxic profile than previous long acting local anesthetics, like bupivacaine, 6,7 and is available as a 0.2% solution for epidural analgesia. However, little information is available on the association of low concentrations of ropivacaine and fentanyl for epidural postoperative analgesia after major abdominal surgery.…”
mentioning
confidence: 99%